Translational regulation using the PUF scaffold and deadenylases - Prigge, Andrew (My University, 2010)
Translation is a key point of regulation in gene expression. A number of regulatory proteins involved in the processes of activation and repression have been characterized through tethered function assays. We designed chimeras using the PUF scaffold to utilize the functions of regulatory proteins to modulate translation and the poly(A) tail. These chimeras possess flexibility in RNA recognigion and are capable of activating or repressing the translation of specific mRNA targets. In parallel, we have identified a number of protein interactions with the Xenopus laevis Cafl deadenylases in an effort to elucidate their deadenylation independent mechanism of repression. Interactions with eukaryotic translation initiation factors suggest a role in preventing translation initiation.
30 p.
Keywords: Biochemistry